Increasing Resource Parents’ Access to Training and Data: An Overview of Two Child Welfare Initiatives - Romano, Elisa; Stenason, Lauren (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2022)
Objectives: Resource parents are critical to young people’s well-being, resilient functioning, and placement stability. However, child welfare often experiences challenges in retaining resource parents, which may be partially due to the limited availability of in-service resources. We describe two in-service training initiatives for resource parents in Ontario (Canada) that can support their important caregiving work. We also present preliminary mixed-methods findings on training reactions and learning.